Assessing the Impact of Fiscal Incentives on the Investment Feasibility of Geothermal Projects in Indonesia: A Value-at-Risk approach - Susmanto, Andi; Hidayatno, Akhmad; Setiawan, Andri D.; Pratama, Dendy Rio Casillas (International Journal of Energy Economics and Policy, 2026)
This study assesses the impact of fiscal incentives on the investment feasibility and risk profile of geothermal power projects in Indonesia. Geothermal energy is central to the country’s clean-energy transition, yet high exploration costs, long development timelines, and limited fiscal support constrain private investment. To address these challenges, a quantitative analysis was conducted using an integrated Discounted Cash Flow (DCF) model and Value-at-Risk (VaR) analysis. A stochastic financial model for a 50 MW geothermal power plant was simulated over 1000 Monte Carlo iterations across five policy scenarios: Business-as-Usual (BAU), Value-Added Tax (VAT) removal, Land and Building Tax (LBT) removal, tax holiday, and a combined total incentive package. Results show that fiscal incentives improve project profitability while affecting financial volatility. The BAU case yields a mean Net Present Value (NPV) of – USD 8.4 million and an Internal Rate of Return (IRR) of 9.39%, whereas the Total Incentive scenario achieves + USD 0.38 million NPV and 10.03% IRR. The VaR analysis indicates reduced downside loss probability but greater dispersion of returns, suggesting a high-risk, high-return profile. Sensitivity results highlight power-plant EPC and drilling costs as dominant risk drivers.